PENUMBUHAN BUDAYA LITERASI MELALUI LOMBA MEMBACA NYARING UNTUK MENINGKATKAN MINAT BACA SISWA SD/MI DI DESA SAWOCANGKRING, SIDOARJO - Amima Na’ma; Fathul Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literacy activities play a crucial role in improving the quality of education, especially at the elementary level. The low reading interest among elementary school students encourages the need for creative and participatory strategies to foster a literacy culture. This research was carried out through a read-aloud competition at SD/MI Sawocangkring Village, Sidoarjo, aiming to enhance students’ reading interest as well as expressive reading skills. The method used was a participatory approach with educational strategies through observation, interviews, and documentation. The results show an increase in reading interest, text comprehension, public speaking skills, and students’ self-confidence. Moreover, the involvement of teachers, parents, and village officials provided real support in creating a sustainable literacy ecosystem. Therefore, the read-aloud competition proved effective as a medium for fostering literacy culture in elementary schools.